1999
DOI: 10.1046/j.1432-1327.1999.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of low‐molecular‐mass trypsin isoinhibitors from oil‐rape (Brassica napus var. oleifera) seed

Abstract: A new low-molecular-mass (6767.8 Da) serine proteinase isoinhibitor has been isolated from oil-rape (Brassica napus var. oleifera) seed, designated 5-oxoPro1-Gly62-RTI-III. The 5-oxoPro1-Gly62-RTI-III isoinhibitor is longer than the Asp2-Pro61-RTI-III and the Ser3-Pro61-RTI-III forms, all the other amino acid residues being identical. In RTI-III isoinhibitors, the P 1 -P 1 H reactive site bond (where residues forming the reactive site have been identified as P n ¼P 1 and P 1 H ¼P n H , where P 1 -P 1 H is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 50 publications
3
41
0
2
Order By: Relevance
“…The identification of protein domains retaining biological activity, and the demonstration that their functional properties are maintained in chimeric macromolecules are essential steps in the engineering of novel biological activities through fusion of small, stable domains to protein partners (9,16,17). Accordingly, we previously reported that the T-knot domain of RTI-III represents the inhibitor reactive site scaffold (12). Here, we demonstrate that RTI-III inhibitor properties are retained even when the reactive site T-knot scaffold (Ser3-Lys35 residues) is fused to a protein partner (i.e., DHFR).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The identification of protein domains retaining biological activity, and the demonstration that their functional properties are maintained in chimeric macromolecules are essential steps in the engineering of novel biological activities through fusion of small, stable domains to protein partners (9,16,17). Accordingly, we previously reported that the T-knot domain of RTI-III represents the inhibitor reactive site scaffold (12). Here, we demonstrate that RTI-III inhibitor properties are retained even when the reactive site T-knot scaffold (Ser3-Lys35 residues) is fused to a protein partner (i.e., DHFR).…”
Section: Resultsmentioning
confidence: 99%
“…Anima) of oil rape (Brassica napus var. oleifera) seed as previously reported (12). Bovine trypsin was obtained from Worthington Biochemical Co. (Freehold, NJ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed Ceciliani et al (1994), and Ascenzi et al (1999) have characterized in rapeseed, serine PIs with features common to MTI-2 (Menegatti et al 1992), and it has recently been demonstrated that the oilseed rape nuclear genome encodes a gene family of PIs (Ceci et al 1999).…”
Section: Discussionmentioning
confidence: 99%